2020
DOI: 10.1055/s-0040-1714257
|View full text |Cite
|
Sign up to set email alerts
|

Early- and Late-Respiratory Outcome in Very Low Birth Weight with or without Intrauterine Inflammation

Abstract: Abstract• IUI is a risk factor for spontaneous preterm birth and contributes to prematurity-associated mortality and morbidity.• HCA greatly affected Apgar’s score and lung management of VLBWI at birth and later on with increased incidence of BPD.• HCA + FUN did not significantly impact on respiratory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…Our measurements confirm and extend observations in previous studies reporting qualitative assessments of respiratory function in infants from mothers with chorioamnionitis 13–15. While they had no RFM data, these studies observed less spontaneous breathing and a greater need for both oxygen supplementation and invasive ventilation in the delivery room for infants affected by chorioamnionitis 13–15. These findings are consistent with the lower breathing effort and oxygenation observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our measurements confirm and extend observations in previous studies reporting qualitative assessments of respiratory function in infants from mothers with chorioamnionitis 13–15. While they had no RFM data, these studies observed less spontaneous breathing and a greater need for both oxygen supplementation and invasive ventilation in the delivery room for infants affected by chorioamnionitis 13–15. These findings are consistent with the lower breathing effort and oxygenation observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…As CCA infants took significantly longer to reach an SpO 2 >80% and their SpO 2 was lower at 5 min after birth, despite receiving higher FiO 2 levels, we found that chorioamnionitis also adversely affected oxygenation, which is in line with previous studies 13 14. This is likely caused by reduced breathing effort, which delays lung aeration and reduces the surface area available for gas exchange.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies indicated that HCA or amniotic cavity infection and neonatal EOS were closely connected [ 6 , 7 ]. Moreover, Apgar score, endotracheal intubation rate, mechanical ventilation rate, pulmonary surfactant application, severe PDA rate, and the incidence of BPD in very low birth weight infants were related to HCA [ 18 ]. Maternal amnionitis led to the low gestational age and low birth weight of preterm infants, and it was an independent risk factor for intraventricular hemorrhage [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of premature infants are antenatally exposed to inflammation of the foetal membranes and umbilical vessels, which fall under the umbrella term 'chorioamnionitis' [5]. Since chorioamnionitis-induced inflammation appears to depress breathing both before and after birth, premature infants affected by chorioamnionitis likely face the combined problems of an immature respiratory system and inflammatory-mediated respiratory depression, which synergistically could suppress effective continuous breathing of neonates at birth [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%